Decentralized Autonomous Organizations How to Approach Decentralized Governance from the Perspective of International Law? - Kilpi, Aleksi (My University, 2021)
This thesis analyzes how Decentralized Autonomous Organizations should be approached from the perspective of international law. Decentralized Autonomous Organizations rely on blockchain technology; thus, the analysis considers the regulation of blockchain technology also. With a descriptive approach the existing regulatory models are analyzed on an international level to further assess how should this rather new form of technology be regulated by different states and authorities. Decentralized Autonomous Organizations challenge the more traditional form of centralized governance, by decentralizing it. This new organization type along with the technology behind it, can bring new challenges to different regulators and raise new legal questions which need to be considered. The analysis provides examples of other phenomenon which have been considered unregulatable, for example the discussions regarding Decentralized Autonomous Organizations resemble the early discussions on the internet and whether it can be regulated. As different examples from around the world are provided and the existing use cases are provided, it will be concluded that Decentralized Autonomous Organizations need international law and further possibilities how to regulate and how to approach from the perspective of international law are provided.
Keywords: Decentralized Autonomous Organizations, international law, blockchain, blockchain technology, governance, smart contracts